(untitled) (Economic and Political Thought, 2019)
The recent financial crisis revealed an important link between the stability of the banking system and real estate lending. An aim of the article is to present tools in the field of banking supervision as the factors that may limit the supply of such loans. The research covered only instruments introduced to the EU legislation through the CRDIV/CRR package; then, the method of comparative analysis has been applied to show the scope of implementation thereof in individual EEA states. The obtained results allow stating that supervisory measures undertaken in relation to capital requirements are characterised by significant flexibility. However, a relatively limited number of countries have decided to use them because of their potential side effects.